2002
DOI: 10.1108/00346650210416994
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical characteristics of roselle (Hibiscus sabdariffa L.)

Abstract: The physico‐chemical characteristics of roselle from Malaysia were studied. The parameters analysed included size, weight, pH, titratable acidity, soluble solids, anthocyanin contents, organic acids and sugars. Succinic and oxalic acids were the predominant organic acids found in roselle while glucose was the major sugar present. The present study was also conducted to determine and quantify the most biologically effective natural antioxidants present in roselle. Ascorbic acid, β‐carotene and lycopene, were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 17 publications
8
91
3
7
Order By: Relevance
“…The most abundant anthocyanin was delphinidin-3-sambubioside (dp-3-sam), which accounted for 71.2% of total peak area, followed by cyanidin-3-sambubioside (cy-3-sam, 16.1%) and delphinidin-3-glucoside (dp-3-glu, 8.7%). Similar to documented studies (Hong and Wrolstad, 1990;Wong et al, 2002), dp-3-sam and cy-3-sam were the main constituents accounting for nearly 90% of total anthocyanins in Roselle extract. In conflict, however, with some previous results (Du and Francis, 1973;Hong and Wrolstad, 1990) cyanidin-3-glucoside (cy-3-glu) …”
Section: Anthocyanin Compositions In Roselle Extractsupporting
confidence: 65%
See 1 more Smart Citation
“…The most abundant anthocyanin was delphinidin-3-sambubioside (dp-3-sam), which accounted for 71.2% of total peak area, followed by cyanidin-3-sambubioside (cy-3-sam, 16.1%) and delphinidin-3-glucoside (dp-3-glu, 8.7%). Similar to documented studies (Hong and Wrolstad, 1990;Wong et al, 2002), dp-3-sam and cy-3-sam were the main constituents accounting for nearly 90% of total anthocyanins in Roselle extract. In conflict, however, with some previous results (Du and Francis, 1973;Hong and Wrolstad, 1990) cyanidin-3-glucoside (cy-3-glu) …”
Section: Anthocyanin Compositions In Roselle Extractsupporting
confidence: 65%
“…Some recent reports showed that the anthocyanins extracted from Roselle exhibited high free radical scavenging capacity against several typical free radicals such as 1,1-diphenyl-2-picrylhydrazyl radical (DPPH), 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS + ), superoxide radical anion (O 2 -) and peroxyl radical (ROO) (Degenhardt et al, 2000;Duh and Yen, 1997;Prenesti et al, 2007;Tsai et al, 2002;Tsai and Huang, 2004;Tseng et al, 1997;Wang et al, 2000). In addition to anthocyanins, the large amount of ascorbic acid in Roselle may also help in preventing autooxidation (Wong et al, 2002;Wong et al, 2003). Several methods have been used for evaluating the capacity of antioxidative compounds, including Trolox equivalent antioxidant capacity (TEAC) assay, ferric ion reducing antioxidant power (FRAP) assay, oxygen radical absorbance capacity (ORAC) assay, crocin bleaching assay, DPPH radical scavenging capacity assay and total antioxidant potential assay (Huang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Higher decrease in pH value of Roselle calyxes extract was recorded for the two cultivar and the two packaging materials and extraction with water and acidic water 2% citric acid at 100 C 0 for 90 min from zero day (control) to the end of storage (after 8 months) of Wong, et al, (2002) found that the low pH value of the drinks was due to the acidic nature of the roselle calyces and the fruits. Roselle is characterised as a highly acidic fruit rich in organic acids: oxalic, tartaric, malic and succinic.…”
Section: The Ph Valuesmentioning
confidence: 99%
“…Succinic acid and oxalic acid were quantified as two predominant organic acids in Roselle. Roselle was found to contain higher amount of ascorbic acid compared to orange and mango ( Wong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the content of anthocyanin in roselle (UKMR-2) pickle was reduced approximately 90% as compared to the original content in fresh roselle UKMR-2, which was 230 mg/100g (Anon, 2009). According to Giusti et al (2001), anthocyanin is relatively unstable and often degrades during processing and storage and it is also categorized as a water-soluble flavonoid pigments (Wong et al, 2002). These factors contributed to the decreased in the anthocyanin during processing of roselle pickles.…”
Section: 10mentioning
confidence: 99%